Pakistan, Sindh Province - Baseline Indicators System : Baseline Procurement Performance Assessment Report - World Bank (World Bank, 2012)
This document provides an assessment of the public procurement system in Sindh province using the baseline indicators system developed by the Development Assistance Committee of the Organization for Economic Cooperation and Development (OECD-DAC). This assessment, interviews and discussions were held with stakeholders from the public and private sectors as well as civil society. Developing country governments and donors have a mutual interest in increasing the effectiveness, efficiency, and transparency of procurement systems. Both have worked together under the auspices of the World Bank and OECD-DAC procurement round table initiative to develop a set of tools and standards to support and guide improvements in procurement systems. These tools include: (i) benchmarking for assessing the structure of public procurement systems, and (ii) monitoring and evaluation of public procurement systems. A key analytical tool developed for benchmarking is the baseline indicators system which comprises four pillars: 1) the legislative and regulatory framework; 2) institutional framework and management capacity; 3) procurement operations and market practices; and 4) integrity and transparency of the public procurement system.